The methods and use of questionnaires for the diagnosis of dental phobia by Japanese dental practitioners specializing in special needs dentistry and dental anesthesiology: a cross-sectional study - Mika Ogawa; Terumi Ayuse; Toshiaki Fujisawa; Shuntaro Sato; Takao Ayuse (BMC, 2022)
Abstract Background Dental phobia is covered by medical insurance; however, the diagnostic methods are not standardized in Japan. Therefore, the aim of this study was to investigate the methods and use of questionnaires for the diagnosis of dental phobia by Japanese dental practitioners specializing in special needs dentistry and dental anesthesiology. Methods We conducted an online survey to obtain information from the members of the Japanese Society for Disability and Oral Health (JSDH, n = 5134) and the Japanese Dental Society of Anesthesiology (JDSA, n = 2759). Response items included gender, qualification, affiliation type, methods of diagnosis and management of dental phobia, use of questionnaire, need to establish standardized diagnostic method for dental phobia, and others. The chi-squared test was used to compare answers between the three groups: JSDH only, JDSA only, and both JSDH and JDSA. Multiple logistic regression analysis was conducted to identify factors associated with the use of an assessment questionnaire. Results Data were obtained from 614 practitioners (JSDH only, n = 329; JDSA only, n = 195; both JSDH and JDSA: n = 90, response rate: 7.8% [614/7,893], men: n = 364 [58.5%]). Only 9.7% of practitioners used questionnaires to quantify the level of dental anxiety. The members of both JSDH and JDSA group used questionnaires more frequently than members of the JSDH only (19% and 7.1%, respectively; Bonferroni corrected p < 0.01). Most practitioners (89.1%) diagnosed dental phobia based on patient complaints of fear of treatment. Furthermore, majority of the participants (73.3%) felt the need to establish standardized diagnostic method for "dental phobia." Multiple logistic regression analysis showed that membership of the JSDH only was negatively related (odds ratio [OR] 0.28, 95% confidence interval [CI] 0.13-0.60), and use of behavioral therapy was positively related (OR 2.34, 95% CI 1.18-4.84) to the use of a questionnaire. Conclusions The results of this study showed that the use of questionnaires was very low, patients' subjective opinions were commonly used to diagnose dental phobia, and a standardized diagnostic criterion was thus needed among practitioners. Therefore, it is necessary to establish diagnostic criteria for dental phobia in line with the Japanese clinical system and to educate dentists about them.